PURIFIKASI DAN PROFIL PROTEIN OVOTRANSFERRIN DARI EGGSHELL MEMBRANE TELUR AYAM RAS DAN BURAS - Risa Fazriyati Siregar; Ahmad Ni’matullah Al–Baarri; Antonius Hintono; Yoyok Budi Pramono; Setya Budi Muhammad Abduh (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2016)
Eggs consumption in Indonesia increases every year resulting in egg shell waste. In addition, the functional components including ovotransferrin existing in this waste has not been yet studied well. This research has been done to explore ovotransferrin in egg shell membrane from local Indonesia and leghorn hens. The ion exchange chromatography using SP-Sepharose Fast Flow was used to purify the ovotransferrin from egg shell membrane. The fractions from salt elution were analyzed for protein concentration and protein profile using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS - PAGE). The result showed that the best concentration of salt elution to obtain ovotransferrin was 0.1 mM NaCl since the single band was detected among other fractions. The ovotransferrin concentration (%) per single egg was also calculated as much as 0.75±0.017 and 0.16±0.005 for leghorn dan local Indonesia hen, respectively. This result may provide the beneficial information to purify ovotransferrin from egg shell membrane which conceivably as a food preservative agent.